Crosslinking and post‐crosslinking of ethylene vinyl acetate in photovoltaic modules. Issue 23 (10th February 2017) - Oreski, G.; Rauschenbach, A.; Hirschl, C.; Kraft, M.; Eder, G.C.; Pinter, G.
ABSTRACT: Ethylene vinyl acetate (EVA) is the dominating material for the encapsulation of solar cells. A better understanding of the crosslinking reaction progress during PV module lamination could lead to promising approaches for shortening of PV module lamination times but also for optimization of the EVA formulation. Therefore, the main aim of this study is to investigate the crosslinking behavior of EVA but also for optimization potentials of the EVA formulation. Currently, a degree of crosslinking higher than 70% obtained from Soxhlet extraction, is used as quality control standard in PV industry. Thermomechanical properties of the investigated EVA films demonstrate a sufficient state of crosslinking already after 5 min, which corresponds to a Soxhlet value of around 50%. Nevertheless, the effect of the remaining, still reactive peroxide crosslinker under service relevant conditions cannot be neglected. Therefore, the behavior of mini‐modules manufactured at different lamination times and stored under various aging conditions is investigated. EVA not fully cured during lamination are undergoing postlamination crosslinking. At the same time, remaining active crosslinker causes discoloration at soldering ribbons after accelerated aging. The crosslinking time in the lamination process may be reduced to ≥6 min, compromising between high throughput in production and the need of avoiding degradation. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44912. Abstract :